Deformity and Clinical Outcomes Following Surgical Correction of Charcot Ankle. Issue 4 (16th October 2019) - Wallace, Stephen; Liskutin, Tomas E.; Schiff, Adam P.; Pinzur, Michael S.
Category: Ankle, Ankle Arthritis, Diabetes, Hindfoot, Trauma Introduction/Purpose: Deformity associated with Charcot Foot Arthropathy leads to a poor quality of life in affected individuals. Deformity in the midfoot appears to be predictive of clinical outcomes following surgical correction. The goal of this retrospective study was to determine if that same methodology could be applied to patients treated for Charcot Foot Arthropathy involving the ankle joint. Methods: Fifty-six consecutive patients underwent surgical reconstruction of Charcot Foot deformity involving the ankle joint by a single surgeon over a fourteen year period. Preoperative patient characteristics and tibiotalar alignment, were recorded. Surgical treatment included single stage debridement of active infection and ankle arthrodesis with application of a circular external fixator when infection was present (39 of 56, 69.6%) or retrograde locked intramedullary nailing in the absence of infection (17 of 56, 30.3%). Clinical outcomes were graded based on limb salvage, resolution of infection and chronic wounds, and the ability to ambulate with therapeutic footwear or accommodative orthoses. The average follow-up was 7.5 (range 1.1-14.0) years. Results: One patient died at 134.3 weeks following surgery of unrelated causes and 8 underwent amputation. Twenty eight of 56 patients (50.0%) achieved a favorable (excellent or good) clinical outcome. There was no significant association between preoperative or postoperative alignment and clinical outcomes. Insulin-dependent diabetics were approximately 3 times more likely to have a poor clinical outcome. Conclusion: Surgical correction of Charcot deformity involving the ankle joint was associated with a high complication rate and risk for failure. The lessons learned from this highly co-morbid patient population with complex deformities can be used as a benchmark for applying modern surgical techniques.